PREPARING A FURNITURE BUSINESS DEVELOPMENT STRATEGY (CASE STUDY: CV. TUNGGAL JAYA MANDIRI) - Damayanti, Elvira Kurnia; Retnowati, Dini; Dwi Puspita, Asri (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
CV. Tunggal Jaya Mandiri is a manufacturing company that produces furniture in the Jetis sub-district, Mojokerto Regency. The products it makes are pretty well known by the public in the market even though it has many competitors in the same field. In 2022, sales fluctuated and did not reach the target. This is because the company currently does not have proper strategic planning. Therefore, it is necessary to have good strategic planning using three stages of strategy preparation: the input stage, the matching stage, and the decision stage. The input stage is used to identify environmental factors internally and externally using the IFE, EFE, and CPM matrices. At the matching set, SWOT and Internal-External matrices are used. The results obtained from the calculations are the total weighted IFE value of 2.72 and EFE of 2.75. The IE matrix shows the company's position in quadrant V. For this quadrant position; the appropriate strategy is to maintain it through market penetration and product development. The alternative approach obtained is processed into the decision stage with the QSPM matrix, and the primary system is to innovate technology-based furniture products with a TAS value of 6.45.